MEMPERKENALKAN SEJARAH PAHLAWAN NASIONAL MR.RADEN ACHMAD SOEBARDJO DJOJOADISOEJO BAGI PESERTA DIDIK MI/SD DI INDONESIA - Nadhirotul Hadiah (As-Sibyan, 2020)
The purpose of making this article an introduction to the history of Achmad Soebardjo to MI / elementary school students is to be used as a sense of nationalism of young people. Achmad Soebarjo is one of the national heroes who played an active role in Indonesia's independence. Achmad Soebardjo, whose full name is Raden Achmad Soebardjo Djojoadisoerjo. Achmad Soebardjo has the title Tuan because he is a graduate of a university in the Netherlands, and his Raden degree is royal while Djojoadisoerjo is a family name. Even from a respectable family, he still joined the movement of people together with the organizations he was a part of. The number of organizations that achmad Soebardjo joined in the role of achmad soebardjo was so great, Achmad Soebardjo was once appointed to manage the place of education shown for Indonesian youth, Achmad Soebardjo also played a role in the preparation of Indonesian independence by the actions and efforts he made to help prepare for Indonesia's independence in the year 1945. And there are some values that can be stabilized in the struggle carried out by Achmad Soebardjo.